2022
DOI: 10.3126/njog.v17i2.52374
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between various biochemical biomarkers and blood pressure in pregnant women

Abstract: Aims: To find out the correlation of C-reactive protein, serum uric acid and serum LDH with hypertensive antenatal patients. Methods: The present study was conducted among preeclamptic and eclamptic antenatal patients. Serum was used for estimation of serum levels of CRP, LDH and Uric acid. The data obtained was compiled and analyzed statistically and was expressed in terms of mean±SD and percentage. Student t-test, Chi-square test, Pearson’s Correlation Coefficient were used and p value less than 0.05 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Also, this compound is an effective photocatalyst, and results have shown that the presence of NF NPs improved performance. It becomes photocatalytic because the energy level of the conduction band (CB) in NF NPs is lower and the energy level of the valence band (VB) is higher, and by reducing the required potential, this causes the transfer of electrons and holes to these nanoparticles (Figure 8b) [111]. Granular activated carbon (GAC) is an attractive adsorbent for removing various pollutants.…”
Section: Pharmaceutical Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this compound is an effective photocatalyst, and results have shown that the presence of NF NPs improved performance. It becomes photocatalytic because the energy level of the conduction band (CB) in NF NPs is lower and the energy level of the valence band (VB) is higher, and by reducing the required potential, this causes the transfer of electrons and holes to these nanoparticles (Figure 8b) [111]. Granular activated carbon (GAC) is an attractive adsorbent for removing various pollutants.…”
Section: Pharmaceutical Contaminationmentioning
confidence: 99%
“…Adsorption Physio-sorption process [37] Ce-uio-66 MOF @Keratin composites Hydrogen bonding, π-π interaction, electrostatic interaction, and pore filling [40] Sodium alginate-bentonite clay (SA-B) nanocomposite hydrogels Exothermic adsorption and electrostatic interactions [46] Cuo-cellulose and chitosan (CS/CE) aerogel Exothermic, entropy-reduction, chemisorption, and single layer [50] Grafted gelatin/MMT nano clay nanocomposites Electrostatic forces and coordination bonding (metal ions of MMT nano clay) Hydrogen bonding interactions [67] Nanocomposite Zn 2+ @HAP@CS Electrostatic attraction (positively charged composite) [68] CS/PVA/rGO/graphene-based aerogels Capillary uptake and then chemical adsorption [101] DPEA-Cell-OSO −3 polymer Hydrogen bonding [104] Nanocomposites Alg/Gel/n-HAP/MNPs Hydrogen bonding Electrostatic interaction [28] Cs/PEG composite membrane [32] Composite biopolymer sponge GO-coated PS [35] Pop magnetic oak tannin gel (Fe 3 O 4 -OT) [75] Polyelectrolyte complexes CS-QSG Adsorption (heterogeneous multilayer) [31] Chitosan derived from mud crab (Scylla serrata) shells adsorbent Adsorption (monolayer and multilayer) [112] Enhancement in the absorption of visible light, robust electrostatic interactions, and charge separation of photogenerated charge carriers [111] Metal-oxide catalysts MnO x -PP Adsorption-enhanced catalytic oxidation [52]…”
Section: Starch-nife Ldh (S/nife-ldh) Compositementioning
confidence: 99%